Implementasi Jaringan Syaraf Tiruan Backpropagation Untuk Memprediksi Jumlah Pemasangan Instalasi Air Pada PDAM Tirtauli - Sianipar, Markus Parulian; Sumarno, Sumarno; Tambunan, Heru Satria (TIN: Terapan Informatika Nusantara, 2021)
In a service company, there are customers who become company consumers. One level of customer satisfaction can be measured from the level of installation of water installations to the customer's house. Therefore, the Regional Drinking Water Company (PDAM) Tirtauli Pematangsiantar needs to solve the problem in overcoming the number of water installations. Artificial Neural Network with backpropagation algorithm is used to predict the number of new water installations. The test results obtained a prediction accuracy of 89% with a 2-10-1 architecture